KONTRIBUSI LITERASI KEUANGAN TERHADAP INKLUSI KEUANGAN DENGAN PENDIDIKAN SEBAGAI VARIABEL PEMODERASI: STUDI KASUS PADA GURU PEREMPUAN DI KABUPATEN KLATEN - Kuntaryanto, Oki; Agung Nugroho Jati; Cahaya Nugrahani; Titik Purwanti; Cucut Prakosa (FAKULTAS EKONOMI UNWIDHA KLATEN, 2025)
Financial literacy is the ability of individuals to manage their finances wisely. One of its important impacts is increasing financial inclusion, which refers to people's access to formal financial services. This study aims to analyze the contribution of financial literacy to financial inclusion by considering education as a moderating variable, specifically among female teachers in Klaten Regency. The research method used is quantitative with multiple linear regression and path analysis approaches. Data were collected through questionnaires distributed to 100 respondents, active female teachers from various elementary and secondary schools in Klaten Regency. The results show that financial literacy has a positive and significant effect on financial inclusion. In addition, educational level strengthens the relationship between financial literacy and financial inclusion, making education an effective moderating variable. This research provides implications that improving financial literacy, especially among female teachers, must be supported by strengthening the educational aspect to create broader financial inclusion.